Le « Tokyo parallèle » des architectes japonais contemporains ou la fabrique figurée du futur de la métropole - Corinne Tiry-Ono (Ebisu: Études Japonaises)
This article examines the discourses, figures, narratives or imaginaries mobilized by Japanese architects to draw the future of Tokyo since the post-war reconstruction. The design and dissemination of large-scale projects reveals a quest for an overarching image for the capital in a space where this is lacking. Depending on the time period and its dominant issues, these architects use fictions or scenarios derived from identifiable figures to create an original – if not always achievable – future vision for Tokyo. These figures – the island, the tower, the line, the village – are drawn in turn from internal or external, past or present urban representations or motifs, and applied to the territory to determine image and future in a concomitant and situated manner.